ANALISIS PENGARUH PEMBERIAN PENGATUR TEGANGAN BLOWER PADA KOMPOR TERHADAP EFISIENSI PEMBAKARAN - Danang Tri Harimurti; Soni Sisbudi Harsono (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2021)
A biomass stove is one of the alternative tools made from bio pellet as a substitute for LPG gas stove (Liquefied Petroleum Gas). Biomass stoves are currently less known by the public due to their traditional use and lack of socialization of biomass fuels. Starting from the problem, biomass stoves currently need further development in order to be used in daily life. Therefore, it is necessary to develop the biomass stove by adding a 12-volt lithium-ion battery as the main power source and a circuit dimmer as a fan speed regulator. The treatment variable in this study is to provide variations in fan speed. Variations used are low, medium, and high fan speeds. The main fuel of the biomass stove is a wood grain bio pellet with the weight of each bio pellet used per treatment as much as 300 grams. The method used in this study used a one-way ANOVA that produced a difference in variation had no real differences and had a noticeable effect on the rate of combustion, the temperature of the fire, and the length of time the water was boiled.